2016
DOI: 10.1111/jop.12513
|View full text |Cite
|
Sign up to set email alerts
|

Limited mouth opening in oral submucous fibrosis: reasons, ramifications, and remedies

Abstract: Limited mouth opening (LMO) in oral submucous fibrosis (OSF) has been attributed to both the submucosal and muscle fibrosis (MF). While reflectory trismus was proposed before as an auxiliary mechanism by another group, the stretch-mediated muscle damage (MSD), histopathological changes in blood vessels (such as endothelial dysfunction, endothelial hypertrophy, and endarteritis obliterans), and upregulated anaerobic isoforms of lactate dehydrogenase (LDH) have been proposed by us as complementary events leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 64 publications
(104 reference statements)
0
34
1
1
Order By: Relevance
“…Epidemiological investigation has revealed that the habit of areca nut chewing is a major etiology factor for OSF development . One of the recent studies has shown that the limited mouth opening is mediated through numerous mechanisms, and TGF‐β is involved in several events, such as myofibroblast transdifferentiation . It is well known that persistent activation of myofibroblasts results in excessive accumulation of extracellular matrix (ECM), which contributes to the pathogenesis of fibrosis .…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological investigation has revealed that the habit of areca nut chewing is a major etiology factor for OSF development . One of the recent studies has shown that the limited mouth opening is mediated through numerous mechanisms, and TGF‐β is involved in several events, such as myofibroblast transdifferentiation . It is well known that persistent activation of myofibroblasts results in excessive accumulation of extracellular matrix (ECM), which contributes to the pathogenesis of fibrosis .…”
Section: Introductionmentioning
confidence: 99%
“…(a) Study design: Randomized control trials (RCTs); (b) Participants: Individual in any age group, diagnosed clinically and/or histopathologically with OSF; (c) Intervention: Aleo vera administrated topically and/or systemically; (d) Comparator: Any medical interventions (systemic, submucosal injection or topical agents), or a placebo control; (e) Outcomes: The primary outcomes included (i) subjective improvement in severity of mucosal pain/burning sensation, using any recognized validated pain scale, (ii) objective changes or improvement in maximal interincisal mouth opening, (iii) objective changes in tongue movement (protrusion), and objective changes in cheek flexibility, and the secondary outcomes included side effects of the intervention; (f) Language: articles published in English language.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, OSF is predominantly seen in population groups from South and Southeast Asia . OSF usually affects young individuals aged 20‐40 years old, with a striking male predilection, and an estimated prevalence of 6.42 per 1000 . The disease process is characterized by juxta‐epithelial inflammatory reaction in the oral mucosa, fibro‐elastic change of lamina propria and epithelial atrophy .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moderate-to-severe OSF is irreversible and current treatment strategies include injections or topical application of steroids, oral subministration of lycopene (16 mg daily) and pentoxyfilline (400 mg 3 times daily) (16,118,119). A previous study demonstrated that RSV epigenetically inhibits Zinc finger E-Box binding homeobox 1 expression to suppress the myofibroblast activity of fibrotic buccal mucosal fibroblasts, and may serve as a dietary supplement for OSF patients (120).…”
Section: Resveratrol As a Chemopreventivementioning
confidence: 99%